PROMOSI DENGAN DESAIN POST INSTAGRAM MELALUI ADOBE ILLUSTRATOR UNTUK MEMPERLUAS PENYEBARAN INFORMASI DI KOS PUTRI MOJO 10 MALANG - Fiona Rose Firta; Umi Khabibah (CV. KAMPUS AKADEMIK PUBLISING, 2025)
The research was aim to give solution for Kos Putri Mojo to develop promotional medium using Instagram The study was an action research consisting of planning, action, observation, and reflection. The data collection method used was questionnaire consisting of elements of Empathy, Impact, Persuasion, and Communication (EPIC).The analysis result on cycle 2 indicated the average EPIC Rate score 4.4. This means that the instagram post design was very effective to be used as a promotional medium.